Archibald Lampman's » ; nature« ; poetry as reflecting the (im)possibility of construing Canadian identity - Domines Veliki, Martina (Array, 2008)
The aim of this paper is to show on the example of Archibald Lampman and William Wordsworth how the two literary traditions intersperse and diverge on the ultimate Romantic subject – Nature. Descriptions of nature in the poems of Lampman and Wordsworth are often interior landscapes or « ; maps of a state of mind» ; (Atwood) important for defining one's identity. In Wordsworth's poetry man's identity is built and re-built on the basis of his close contact with Nature that soothes him and provides comfort for the years to come. On the other hand, Lampman's poetry speaks about the difficulty of coming to terms with Nature, of taming the unpredictable, cruel and often meaningless landscape. There exists in Lampman's poetry an attempt to reconcile with Mother-Nature and seek guidance from it, a prominent Wordsworthian trait which is juxtaposed to the feeling of being swallowed up by Nature's unconscious cruelty and bareness. The instability of the Canadian concept of « ; identity» ; and the inability to define what it really is might be the result of this double-sided view of Nature.